Simulation of (electro)chromatography by means of CFD - Astrath, Dirk-Uwe; Schneider, Thomas; Arlt, Wolfgang (2006)
Computational Fluid Dynamics is employed to develop models of (electro)chromatographic processes that take the radial coordinate into account. The liquid chromatographic models are based on the results of computed tomography experiments that proved the packing structure of the invastigated columns to be heterogenous. In the context of electrochromatography, CFD is used to evaluate the potential of the technique to be scaled up to columns sizes that have not yet been used in practice. © 2006 Elsevier B.V. All rights reserved.
Keywords: Computational Fluid Dynamics; Computed Tomography; Electrochromatography; Liquid Chromatography